2000
DOI: 10.1001/archpedi.154.6.549
|View full text |Cite
|
Sign up to set email alerts
|

Parental and Self-report of Sleep in Children With Attention-Deficit/Hyperactivity Disorder

Abstract: Sleep disturbances, particularly at bedtime, are frequently reported by both parents and children with ADHD. Children undergoing evaluation for ADHD should be routinely screened for sleep disturbances, especially symptoms of sleep-disordered breathing. The causes of sleep-onset delay in children with ADHD should be considered in designing intervention strategies for children with difficulty falling and staying asleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
221
2
18

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(258 citation statements)
references
References 32 publications
(40 reference statements)
17
221
2
18
Order By: Relevance
“…Also, self-reported sleep difficulties are more frequent for ADHD children than for others [38]. Like Wiggs et al [48], we also found that parents of children with ADHD experienced more difficulties related with bedtime than parents of healthy children.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Also, self-reported sleep difficulties are more frequent for ADHD children than for others [38]. Like Wiggs et al [48], we also found that parents of children with ADHD experienced more difficulties related with bedtime than parents of healthy children.…”
Section: Discussionsupporting
confidence: 82%
“…Little need for sleep, difficulties falling asleep, restless sleep, frequent awakenings and fatigue in the morning are commonly reported problems [16,30,46]. The children themselves also report sleep difficulties more often than children without ADHD [38]. Self-report studies show that more than half the children with ADHD reported that they experienced sleep difficulties [5,20,30], which could be of great theoretical importance in the clinical work.…”
Section: Introductionmentioning
confidence: 99%
“…49 Our data failed to demonstrate an association between inadequate sleep and ADHD in either age group in multivariate models. Studies relying on parental report of sleep behavior 18,38,50 support an association between a diagnosis of ADHD and sleep problems in children. Parents of children with ADHD report sleep problems in 25% to 50% of these children, 20 but these findings are not supported when more objective measurements such as polysomnography are used.…”
Section: Sleep and Comorbiditymentioning
confidence: 99%
“…Conversely, ADHD symptoms and psychostimulant medication may exacerbate sleep impairment. Although as many as 50% of parents of children and adolescents with ADHD report sleep problems, [18][19][20] studies using more objective polysomnography have failed to demonstrate differences in sleep architecture between children with and without ADHD. 20 Similarly, both research and clinical experience supports the relationship between sleep problems and mood and anxiety disorders, although it is unclear whether the sleep problem or the psychiatric disorder is the primary problem.…”
mentioning
confidence: 99%
“…Children with ADHD have more sleep problems compared with their peers [3]. Their parents report sleep problems in 25-55% [4] and the prevalence of sleep problems, such as falling asleep and maintaining sleep, can vary between 55% and 74% [5][6][7]. The primary sleep disorder symptoms are resistance against sleep, an increase in the amount waking at night, and sleepiness during the day [8,9].…”
Section: Introductionmentioning
confidence: 99%